Fast hydrothermal liquefaction for production of chemicals and biofuels from wet biomass – The need to develop a plug-flow reactor. (August 2016) - Tran, Khanh-Quang
Highlights: No clear winner in HTL of biomass can be identified so far. Process intensification can help HTL to win. Fast heating combined with short residence time helps increase biocrude yield of HTL. Static mixing of pre-heated water with biomass solution offer high heating rates. Key issue for HTL of biomass is to develop a plug-flow reactor. Abstract: Hydrothermal liquefaction (HTL) is a promising technology for converting wet plant biomass directly to liquid fuels and chemicals. However, some aspects of the technology are not fully understood and still disputed. The reactor material constraints and difficulties coupled with the formation of unwanted products are the main challenges limiting the applications of the technology. In addition, heat and mass transfer limitations in the reaction system result in a lower conversion efficiency and selectivity, of which the later would make it difficult and expensive for products separation, purification, and/or modification of the products. This paper discusses the challenges and current status of possible solutions to the challenges, focusing on the need of developing a special plug-flow reactor for scaling up of the HTL process.